Maternal depressive symptom trajectories and associations with child feeding - Katelyn Fox; Chantelle N. Hart; Suzanne Phelan; Alison K. Ventura; Rena Wing; Elissa Jelalian (BMC, 2024)
Abstract Background Responsive feeding, when caregivers attend to children's signals of hunger and satiation and respond in an emotionally supportive and developmentally appropriate way, is associated with the development of healthy eating behaviors, improved diet quality, and healthy weight status for children. However, gaps in the literature remain on how factors, such as maternal depressive symptoms and child temperament, influence feeding interactions. Methods This longitudinal secondary data analysis explored the association between maternal depressive symptom trajectory and child temperament with maternal feeding practices in women with obesity who participated in a prenatal lifestyle intervention trial. Mothers self-reported depressive symptoms at baseline, 35 weeks gestation, and 6, 12, and 18 months postpartum. At 18- and 24-months postpartum, mothers completed self-reported assessments of feeding practices and child temperament and completed in-home video-recorded meals with their child, coded using the Responsiveness to Child Feeding Cues Scale. We used group-based trajectory modeling to identify distinct trajectories of depressive symptoms and generalized regressions to assess the association between symptom trajectory group and feeding. We also explored interactions between depressive symptoms and child temperament. Results Three distinct trajectories of depressive symptoms were identified: No-Minimal and Decreasing, Mild-Moderate and Stable, and Moderate-Severe and Stable. At 18-months, when compared to the No-Minimal and Decreasing group, membership in the Moderate-Severe and Stable group was associated with higher observed responsiveness to child satiation cues ( $$B$$ =2.3, 95%CI = 0.2, 4.4) and lower self-reported pressure to eat ( $$B$$ =-0.4, 95%CI= -0.7, 0.0). When compared to the No-Minimal and Decreasing group, membership in the Mild-Moderate and Stable group was associated with higher self-reported restriction ( $$B$$ =0.4, 95%CI = 0.0,0.7). The associations between trajectory group membership and feeding practices did not reach statistical significance at 24 months. Associations between depressive symptoms and restriction were moderated by child effortful control at 18 months $$(B=0.2, 95% CI (0.0, 04)$$ ) and surgency at 24 months $$B=-0.3, 95% CI (-0.6, 0.0)$$ ). Conclusion A Moderate-Severe and Stable depressive symptom trajectory was associated with more responsive feeding practices and a Mild-Moderate and Stable trajectory was associated with higher restrictive feeding. Preliminary evidence suggests that depressive symptoms impact mothers' ability to match their use of restriction to the temperamental needs of their child.